Business Environment, Economic Agglomeration and Job Creation around the World - Clarke, George; Li, Yue; Xu, Lixin Colin (World Bank, Washington, DC, 2014)
Based on a comprehensive worldwide firm survey, this paper looks at how the business environment and economic agglomeration affect job creation, holding constant conventional determinants of firm growth, such as firm ownership, size, and age. The analysis finds that economic agglomeration is most important, especially modern telecommunications, access to export markets, concentration of economic activity in large cities, and capacity agglomeration (the concentration of large firms in a city). Although the business environment affects job growth less than agglomeration does, some elements of the business environment matter, such as labor flexibility, unionization, and local skill levels. There is strong heterogeneity in job creation across firm size and age.